Pain perception and depression in patients with hidradenitis suppurativa. (1st January 2020) - Nielsen, R.M.; Lindsø Andersen, P.; Sigsgaard, V.; Riis, P.T.; Jemec, G.B.
Summary: Hidradenitis suppurativa (HS) is a chronic skin disease. It causes painful boils in specific body areas such as the armpits and the groins. This disease affects about 1% of people in the U.K. It is more common in women. HS causes pain, but few studies have looked at this aspect. Depression and anxiety affects how pain is experienced. The patient's age and sex can also influence the experience of pain. The authors aimed to study pain in patients with HS. They handed out questionnaires in a HS specialist clinic in Roskilde, Denmark (Oct 2017 – Mar 2018). Patients described their pain and difficulty of HS, and reported any symptom of depression and anxiety. Pain was described with different words. The most common words were 'shooting' (83%), 'itchy' (79%) and 'blinding' (75%). The study revealed that pain in HS relates to severity of HS and to symptoms of anxiety and depression. The authors found that the pain experience of HS patients can be divided into two different pain qualities: the so‐called nociceptive and neuropathic pain. These two pain types are usually treated with different medications: anti‐inflammatory drugs (e.g. aspirin) and antidepressants. In general, HS patients are more often depressed than other people. HS patients are likely to benefit from different pain relievers including both anti‐inflammatory drugs and antidepressants to treat their pain. However, more studies are needed to make definite recommendations on treatment of HS pain. This summary relates to the study: Pain perception in patients with hidradenitis suppurativa